Pengaruh Kejelasan Sasaran Anggaran, Sistem Pelaporan dan Partisipasi Masyarakat Pada Akuntabilitas Pengelolaan Dana Desa - Agus Suma Arta, I Made; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 26 No 1 (2019), 2019)
This study aims to determine the effect of the clarity of budget targets, reporting systems, and community participation in the accountability of village fund management in Seririt District, Buleleng Regency. The study sample was 20 villages in Seririt District with 80 respondents. The method of determining the sample uses the saturated sample method and data collection using a questionnaire. Data were analyzed using multiple linear regression analysis. Based on the results of this study indicate that the clarity of budget targets, reporting systems, and community participation has a positive effect on the accountability of village fund management. This shows that the better the clarity of budget targets, reporting systems, and community participation, the better accountability of village fund management in Seririt District, Buleleng Regency. Keywords : clarity of budget targets, reporting systems, community participation, accountability